HUBUNGAN ANTARA PENGETAHUAN PERSONAL HYGIENE DENGAN KEJADIAN INFEKSI CACING USUS (Studi Observasional Analitik pada Murid di SDN Kuningan 03 Semarang) - Azizia Layaly Chilwa; Pujiati Abbas (PT. Hasba Edukasi Mandiri, 2026)
Intestinal helminth infections, classified as Soil-Transmitted Helminths (STH), remain a public health problem among elementary school children in tropical regions. Limited knowledge of personal hygiene is suspected to increase the risk of infection. This study aimed to analyze the relationship between personal hygiene knowledge and the incidence of intestinal helminth infections among students at SDN Kuningan 03 Semarang. This analytical observational study with a cross-sectional design involved 60 students in grades IV–VI selected using consecutive sampling. Personal hygiene knowledge was assessed using a 20-item questionnaire that had been tested for validity and reliability, while intestinal helminth infection was determined through stool examination. The association was analyzed using the Coefficient of Contingency test (p < 0.05). Most respondents had good knowledge (83.3%), while 16.7% had moderate knowledge. Intestinal helminth infection was found in 6.7% of respondents, all caused by Ascaris lumbricoides. A significant relationship was identified between personal hygiene knowledge and the incidence of intestinal helminth infection (p < 0.001; C = 0.513), with all infection cases occurring in the moderate knowledge group. Strengthening personal hygiene education is necessary to support the prevention of helminth infections among elementary school children.